DYNAMIZATION OF ISLAMIC RELIGION EDUCATION: A Critical Study on Genealogy of Islamic Boarding School’s Scholarly Tradition in Lombok - Murdianto, Murdianto; Iskandar, Muhamad Rozi (State Islamic University North Sumatra, 2021)
Abstract: This study departed from a reality about the pesantren’s scholarly tradition genealogy with unknown scholarly source. Considering such academic restlessness, the question to be answered by the author is “where does the pesantren’s scholarly tradition genealogy existing in Lombok come from? This study was a qualitative research with field research and used such approaches as historical philological, cultural and sociological. This study represents that the pesantren’s scholarly tradition genealogy in Lombok is affected by Javanese Pesantren’s scholarly tradition, Makassar Islam, and Middle East education. However, some dynamics occur in Pesantrens in Lombok, so that the reform of scholarship tradition is required, to keep the pesantren existing in the future.Keywords: genealogy, scholarly tradition, pesantren, islamization, Lombok